Entomotherapy and its potential applications in Panama - Atencio, Randy (2023)
Objective. To analyze the application of entomotherapy and its potential in Panama. Methods. The study is a brief analysis of the application of entomotherapy worldwide and the establishment of a list of 20 potential arthropod species that could be used for this purpose in  Panama, compiling a total of 26 scientifc articles from digital databases associated with the subject. Results. Entomotherapy encompasses the study of the medicinal use of insects and other arthropods in continents such as Africa, America, Asia, Europe and Oceania. Although there are ample references to the use of insects and other arthropods for medical treatments within the traditions of various human groups, in Panama the information associated with this subject is very limited, despite being a diverse country both in culture and in species of arthropods, mainly insects. Conclusions. Twenty examples of arthropods used in entomotherapy in different regions of the world and some in Panama are presented, with potential to be used in pharmacological studies for the treatment of certain pathologies in the country.